2006
DOI: 10.1128/jvi.01370-06
|View full text |Cite
|
Sign up to set email alerts
|

A New Group B Adenovirus Receptor Is Expressed at High Levels on Human Stem and Tumor Cells

Abstract: CD46 is used by human group B adenoviruses (Ads) as a high-affinity attachment receptor. Here we show evidence that several group B Ads utilize an additional receptor for infection of human cells, which is different from CD46. We tentatively named this receptor receptor X. Competition studies with unlabeled and labeled Ads, recombinant Ad fiber knobs, and soluble CD46 and CD46 antibodies revealed three different subgroups of group B Ads, in terms of their receptor usage. Group I (Ad16, -21, -35, and -50) nearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
153
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(166 citation statements)
references
References 44 publications
10
153
2
1
Order By: Relevance
“…As suggested by a recent study, these results may indicate utilization of the unknown group B receptor 'X', used specifically by HAd3, HAd7 and HAd14 in this tropic phenomenon. 17 We also found high levels of the group D representative HAd37 in the spleen as well as the liver, levels similar to those quantified for HAd5. Like group B Ads, HAd37 also uses CD46 as a receptor, but i.v.…”
Section: Had3 and Sad23 Activate Complement In Human Serumsupporting
confidence: 82%
See 1 more Smart Citation
“…As suggested by a recent study, these results may indicate utilization of the unknown group B receptor 'X', used specifically by HAd3, HAd7 and HAd14 in this tropic phenomenon. 17 We also found high levels of the group D representative HAd37 in the spleen as well as the liver, levels similar to those quantified for HAd5. Like group B Ads, HAd37 also uses CD46 as a receptor, but i.v.…”
Section: Had3 and Sad23 Activate Complement In Human Serumsupporting
confidence: 82%
“…Ad serotypes from all human subgenera use CAR as a receptor with the exception of group B Ads and some group D Ads (for example, HAd37) that use a variety of receptors including CD46, sialic acid and the unknown receptor 'X'. [15][16][17] Multiple Ad serotypes are currently under investigation for their potential ability to uniquely target various tissues and/or evade HAd5-specific innate and adaptive immune responses. 18,19 To date, various members of groups A-F have been vectorized and evaluated in vitro and/or in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Both others and we have shown that Ad vectors containing the Ad35 fiber or fiber knob (Ad5/35) efficiently transduce human and non-human primate HSPCs in vitro. [7][8][9][10] Integration site analysis Genomic DNA was isolated from GFP 1 hCD46tg colonies using the DNeasy Blood and Tissue Kit (Qiagen, Valencia, CA). These CFU colonies were obtained from Lin 2 /GFP 1 BM cells of in vivo transduced hCD46tg animals.…”
Section: Introductionmentioning
confidence: 99%
“…The present study indicates that the interaction of penton base RGD motifs in Ad35 with integrins is not largely involved with the cellular binding and uptake of Ad35. Segerman et al 32 and Tuve et al 33 also demonstrated that the presence of divalent cations, which increases the affinity of integrins to their ligands, did not affect the cellular binding of subgroup B Ads. Properties of CD46 also contribute to the lack of necessity of interaction between penton base RGD motifs and integrins for uptake of Ad35.…”
Section: Discussionmentioning
confidence: 97%